Factors affecting the achievement of sporting excellence for players artistic gymnastics - Ibrahim, Thryr (Journal of Physical Education, 2015)
Gymnastics, despite being of the training for basic skills and a series of movements for only that Upgrading can be achieved only through constructive cooperation between researchers and trainers as the preparation methods must be characterized by balance and inclusiveness for all factors. The aim of the research: getting to know factors affecting the achievement of sporting excellence for gymnastics players and understanding the order of the factors affecting the achievement of sporting gymnastics players excellence for in proportion to the contribution of each factor separately. The researcher used the descriptive method to reach the aims of research and the research sample included (44) individuals representing coaches and players, and adopted a researcher on the list include many factors were reduced by offering to become experts on the list (10) factors and after distribution of the questionnaire and to obtain answers and treated statistically possible to arrive at the following factors: First : physical preparation, second: Arrange technical (skill and tactical), Third: physical measurements and specifications, fourth :compatibility intra muscular nerve, fifth: physiological efficiency, sixth: Alhalpalnevsip, seventh : Nutrition and order ofthe day for the player, eighth: physical condition of the player, ninth: competitions, tenth: other factors (each variable potential occurrence